MP14: UTILIZATION OF THE INVASIVE CARDIAC LABORATORY FOR IMMEDIATE CARDIAC CATHETERIZATION. Issue 3 (March 2016) - Friedman, D; Bierzynski, A; Coplan, N
Abstract : Purpose of Study: Immediate cardiac catheterization is indicated for patients presenting with ST elevation (STE) myocardial infarction, and door-to-balloon time should be <90 min. Patients with non-ST elevation myocardial infarction (NSTEMI) can often be stabilized with medication, and only require urgent invasive evaluation if there is persistent chest pain(despite medical therapy) or hemodynamic or electrical instability. Immediate cardiac catheterization for patients presenting to the ER with chest pain is available in many hospitals, but it involves a large investment of resources which need to be properly utilized. This study evaluated patients sent for urgent invasive evaluation to determine how the facility is utilized. Methods Used: In a retrospective chart review, charts from all STEMI code patients presenting between the dates 1/1/15–9/1/15 were studied. The presenting EKG was evaluated to determine whether STE criteria (as per ACC guidelines) were met. The charts were reviewed for angiographic data to determine whether there was ≥90% stenosis of a coronary artery (≥90%) or not (⩽90%). Clinical parameters were studied to determine if there were any differences between the groups. Summary of Results: The study group included 50 patients who went to the cardiology catheterization lab emergently secondary to an indication of STE; 33/50 (66%) patients met guideline criteria for ST elevation (STE+) while 17/50 (34%) did not (STE−). In the STE+ group, 29/33 (88%) had ≥90% occlusion of a coronary artery, while 10/17 (59%) in the STE-group had this degree of stenosis. The sensitivity and specificity of STE for ≥90% coronary artery occlusion on angiography was 74% and 64% respectively. The PPV of STE for >90% stenosis was 88%, while the NPV was 41%. Conclusions: Significant STE in the proper clinical situation is a Class 1 indication for immediate coronary catheterization. However, 34% referred for immediate catheterization in this study did not meet ACC criteria for STEMI. Although a significant % in the NSTEMI group had ≥90% stenosis, urgent catheterization is only indicated in this group when there is a clinical parameter which dictates the necessity of immediate evaluation.